Law, agency and sustainability: the role of law in creating sustainability agency - Salminen, Jaakko (Edward Elgar Publishing, 2021)
This chapter focuses on the role of law on sustainability agency. Earlier research has focused primarily on law as an instrument for calibrating existing agency towards sustainability ex post, for example through regulatory interventions geared towards steering actors towards lower carbon emissions or increased social protection. We contrast this established view by positing the central role of law for creating sustainability agency in the first place. For example, the private law institutions of contract and corporation have for long maintained that economic actors are not liable for externalities, such as the social, environmental, cultural or economic problems attributed to production. In doing so, law creates complex agency that is central for all economic production and for which sustainability related functions are not obligatory but voluntary, unless regulation later on counters the initial voluntary approach to sustainability. In order to develop approaches towards sustainability, it is imperative to focus on both of these two aspects of law and sustainability agency, that is, recognize law not only as an instrument for steering ex post but also as a creator of specific sustainability mindsets ex ante. This is especially important in relation to new forms of organization, such as global value chains and digital platforms, that can override sustainability regulation designed to counter the sustainability deficits of earlier forms of organization, such as centralized mass production.